2021 MEDAM Assessment Report on Asylum and Migration Policies in Europe. The EU and Turkey: Toward sustainable cooperation in migration management and refugee protection - Matthias Lücke; Alberto-Horst Neidhardt; Martin Ruhs; Saime Özçürümez; Olivia Sundberg Diez (Kiel Institute for the World Economy (IfW), 2021)
When the von der Leyen European Commission took office on December 1, 2019, it committed to delivering a "fresh start on migration" through a New Pact on Migration and Asylum. It aimed to forge a new consensus on the future of EU migration and asylum policies, after years of deadlock caused by stark divisions among states and across EU institutions. After several postponements due to the sudden priorities resulting from the COVID-19 pandemic, the European Commission presented the New Pact on September 23, 2020. The 2021 MEDAM Assessment Report on Asylum and Migration Policies in Europe "The EU and Turkey: Toward sustainable cooperation in migration management and refugee protection" analyses the major changes proposed by the New Pact, as well as the progress achieved thus far in negotiations. The report also provides new data and research to inform ongoing policy debates about whether and how to reform EU-Turkey cooperation on irregular migration and refugee protection. Building on the analysis of past trends and experiences, the report discusses current challenges and opportunities for future cooperation-focusing on the EU-Turkey Statement, which was agreed between the EU and Turkey in 2016 and remains the basis for policy cooperation on migration. – – Als die Kommission von der Leyen am 1. Dezember 2019 ihr Amt antrat, verpflichtete sie sich, durch ein neues Migrations- und Asylpaket einen "Neuanfang in der europäischen Migrationspolitik" zu ermöglichen. Ziel ist es, einen Konsens in der EU-Migrations- und Asylpolitik zu erreichen. Nach mehreren Verspätungen - verursacht durch die Corona-Pandemie - stellte die Europäische Kommission das neue Migrations- und Asyl-Paket am 23. September 2020 vor. Der 2021 MEDAM Assessment Report on Asylum and Migration Policies in Europe " The EU and Turkey: Toward sustainable cooperation in migration management and refugee protection" analysiert die wichtigsten Reformvorschläge des Pakets und ihre Umsetzbarkeit. Der Bericht präsentiert zudem neue Daten und Forschungsergebnisse zur Zusammenarbeit zwischen der EU und der Türkei im Bereich der irregulären Migration und des Flüchtlingsschutzes. Die Autoren diskutieren aktuelle Herausforderungen und Möglichkeiten für die zukünftige Zusammenarbeit - mit Fokus auf dem EU-Türkei-Abkommen, das 2016 zwischen der EU und der Türkei vereinbart wurde und Grundlage für die politische Zusammenarbeit im Bereich Migration bleibt.
Keywords: 320